2013
DOI: 10.3329/bjp.v8i4.16422
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of leaf extract of <i>Newbouldia laevis</i> on the metabolic activities of alpha-glucosidase and alpha-amylase

Abstract: In this study, the effect of ethanol extract of the leaves of Newbouldia laevis on the activity of α-amylase and α-glucosidase was investigated. Inhibitory effect of N. laevis extract on α-glucosidase was tested in vitro using baker's yeast α-glucosidase and rat intestinal α-glucosidase while α-amylase inhibitory effect was assayed using rat pancreatic α-amylase. α-Glucosidase inhibitory effect of the extract was also tested in vivo in diabetic and non-diabetic rats. N. laevis extract exhibited good α-glucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…Newbouldia laevis (Bignoniaceae), Ocimum gratissimum (Lamiaceae), and Carica papaya (Caricaceae) are medicinal plants commonly found in Nigeria. These plants have been used ethnomedicinally in the treatment of several disease conditions including ulcers, burns, diarrhea, bleeding, haemorrhoids, dysentery, abdominal pains, cough, colds, pruritus, stress, headache, pneumonia, conjunctivitis, diabetes mellitus, epilepsy and convulsions (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newbouldia laevis (Bignoniaceae), Ocimum gratissimum (Lamiaceae), and Carica papaya (Caricaceae) are medicinal plants commonly found in Nigeria. These plants have been used ethnomedicinally in the treatment of several disease conditions including ulcers, burns, diarrhea, bleeding, haemorrhoids, dysentery, abdominal pains, cough, colds, pruritus, stress, headache, pneumonia, conjunctivitis, diabetes mellitus, epilepsy and convulsions (4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Various scientific studies have shown that N. Laevis possesses antimicrobial, antidiabetic, antioxidant, and antimalarial activities (11)(12)(13)(14). O. gratissimum has been reported to show antidiabetic, antioxidant, anxiolytic, sedative, anti-inflammatory, hepatoprotective, antitumor, gastroprotective, hypolipidemic, insecticidal, nematicidal, and antibacterial activities (4,5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…There is documented evidence that polyphenols slow down glucose absorption by competitive inhibition of the intestinal brush border membrane sodium-glucose co-transporter (SGLT 1) [80] as well as inhibition of disacharidases [81]. Kolawole and Abanji (2013) [82] reported the inhibition of alpha glucosidase and alpha amylase enzymes by the ethanolic leaf extract of N. laevis on sucrose fed rats. Phenolic compounds are known to directly cause regeneration of alloxan damaged islet beta cells by their action as antioxidants and free radical scavengers causing restoration of pancreatic beta cell function [83].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-amylase inhibitory activities of ascidians (Prabhu and Ananthan, 2014), Gossypium arboreum (Kazeem et al, 2013), Newbouldia laevis (Kolawole and Akanji, 2013) and Lantana camara (Swamy and Sinniah, 2015) were reported.…”
Section: Discussionmentioning
confidence: 99%